Description of Dengue Hemorrhagic Fever Cases in Health Centers in the East Pekalongan Sub-District in 2023 - Irawan, Teguh; Indriyani, Yulis; Angraeni, Diva Alya; Amalia, Putri Rika; Zahro, Fatimata; Mutiafani, Amelia; Yusuf, Muhammad Lutfi (PROMOTOR, 2025)
In terms of public health, Dengue Hemorrhagic Fever (DHF) is a problem in Indonesia. The Aedes aegypti mosquito infected with dengue virus is the vector of dengue hemorrhagic fever (DHF).  DHF is usually found in tropical climates, as vector characteristics are influenced by rainfall, temperature, and rapid movement. Data shows that Asia is the center of the most cases of dengue fever every year, and Indonesia is still one of the main transmission areas. In 2017, the dengue incidence rate in Pekalongan City was 1.44 cases per 10,000 population, and there were 44 confirmed cases in the Pekalongan City Health Center area, consisting of 18 males and 16 females. Therefore, this study aims to describe dengue hemorrhagic fever (DHF) cases at the health center in the east Pekalongan sub-district area in 2023, including the number of cases, age, gender, and time of occurrence of cases. This study uses a descriptive method in which secondary data on DHF patients recorded at the Noyontaan, Tondano, and Sukorejo health centers are obtained and then analyzed descriptively using the SPSS version 24 application. Based on the results of the research, the number of DHF cases at the Puskesmas of East Pekalongan Subdistrict in 2023 was quite high, as many as 49 cases, with the highest number of DHF cases found in the Tondano health center area. The number of DHF patients occurred in the adolescent age group of 10-18 years as many as 20 cases (40.8%) and 25 cases (51.0%) of males. The high number of DHF cases indicates the need for more intensive disease prevention and control efforts, especially in the adolescent age group, as well as paying attention to the increase in cases in certain months.